PENGARUH FITUR LAYANAN DAN KEMUDAHAN MENGGUNAKAN M-BANKING BSI TERHADAP KEPUASAN NASABAH - Afifah Miftakhul Jannah; Dian Nova Hastari (LPPM - STIE SAKTI ALAM KERINCI, 2023)
This study aims to determine the effect of service features and convenience on customer satisfaction in transactions using Bank Syariah Indonesia M-Banking. The objects in this study are customers who use m-banking BSI throughout Soloraya. In this study, 149 samples were taken and the data were tested using validation and reliability tests. As for the effect of the t test, it was processed using SPSS version 26. The results showed that the research on service features and convenience had an influence on customer satisfaction with BSI m-banking users throughout Soloraya.